Characterization and horizontal transfer of class 1 integrons in Escherichia coli isolates from cooked meat products - Yu, Tao; Zhang, Jiayang; Jiang, Xiaobing; Wu, Junmei; Dai, Zhigang; Wu, Zhenbin; Liang, Yu; Wang, Xuannian (The Journal of Infection in Developing Countries, 2016)
Introduction: Escherichia coli is a commensal bacterium in humans, animals, and the environment that is one of the microorganisms commonly resistant to antimicrobials. Cooked meat products, which are popular in China, are easily contaminated by E. coli during processing and storage. Methodology: In this study, a total of 75 E. coli isolates from cooked meat products in Henan province, China, were assayed for the presence of and horizontal transfer of class 1 integrons. Results: Class 1 integrons were detected in 11 (14.7%) of these isolates, and contained four groups of resistance gene cassettes, including dfrA17-aadA5, dfrA1-aadA1, dfrA12-orfF-aadA2, and an uncommon array of aacA4-catB8-aadA1. The transfer frequency of selected integron-positve donors ranged from 10-6 to 10-4 transconjugants per recipient cell, and the integron-containing DNA from the donors could be transferred to E. coli J53Azr with the transformation frequency of 10-7 to 10-5. Conclusions: Class 1 integrons could be transferred to recipient E. coli J53 by conjugation and natural transformation. These findings suggest the role of commensal E. coli isolates from cooked meats as an important reservoir for integrons and the possible transfer of antimicrobial resistance genes to humans via the food chain.